PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN SUPERVISI AKADEMIK KEPALA SEKOLAH TERHADAP KINERJA GURU MAN 2 PALU - Risma Triamandani; Isnada Waris Tasrim; Hamdi Rudji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of transformational leadership and academic supervision by school principals on teacher performance at MAN 2 Palu, both partially and simultaneously. The study employed a quantitative approach using a survey method. The research subjects consisted of all 89 teachers at MAN 2 Palu, taken as a total sample. The research instrument was a Likert-scale questionnaire (1–5) that had been tested for validity and reliability. Data were analyzed using multiple linear regression with the assistance of SPSS version 26. The results showed that transformational leadership had a positive and significant effect on teacher performance (t = 2.998; p = 0.000), as did academic supervision (t = 2.103; p = 0.038). Simultaneously, both variables had a significant effect on teacher performance (F = 10.261; p = 0.000), with a coefficient of determination (R²) of 0.174, indicating that 17.4% of the variance in teacher performance was explained by these two variables. In conclusion, transformational leadership and academic supervision are important factors in improving teacher performance, so strengthening both aspects should continue to be pursued by school principals.